Investigation on Construction of the Food Freeze Sublimation Drying Equipments and Heat Transferring - 韩耀明 (Zhileng xuebao)
The match of cryotrap and desiccator,the way of heat transfer on heating board,and heat system design were analyzed to solve the problems of design,manufacturing technique,and structure of the food freeze sublimation drying equipments in the freeze-dried food production process. The comparison experiment for conduction and radiation heat transfer was conducted. The result shows that radiation heat transfer is better than conduction heat transfer between heating board and aluminum tray.